Increasing Children's Ability to Recognize Letters Through the Traditional Lontar Boat Game (JOYCED: Journal of Early Childhood Education, 2025)
This research is motivated by the lack of recognizing letter recognition among children. Then this study aims to explores the effectiveness of the traditional palm boat game in enhancing letter recognition skill. Using Classroom Action Research (CAR) conducted over two cycles each comprising planning, implementation, observation, and reflection the study involved early childhood students at Dharma Wanita Ngompro 2 Kindergarten. The findings revealed significant improvements in the children's ability to recognize letters. During the first cycle, participants demonstrated progress, though some required additional guidance. By the second cycle, nearly all children achieved proficient letter recognition, alongside marked increases in motivation and learning engagement. The study highlights the traditional palm boat game as an innovative, enjoyable, and effective pedagogical tool for early literacy development. Its integration into educational strategies both in classrooms and at home can foster foundational skills while preserving cultural play-based learning. Educators and parents are encouraged to adopt this method to support children’s cognitive and linguistic growth dynamically and meaningfully.
Keywords: traditional games; children’s ability; boat game